The International Business Ethics Index: European Union - Tsalikis, John (Journal of business ethics, 2007)
The present study expands the systematic measurement of consumers’ sentiments towards business ethical practices to the international arena. Data for the Business Ethics Index (BEI) were gathered in three countries of the European Union (UK, Germany, Spain). The Germans were the most pessimistic while the British were the most optimistic about the future ethical behaviour of businesses.